Hepatic hydatid cyst: a masquerader - Kanhaiya, Krishan Kumar; Kandoriya, Bhimsi; Pandey, Vineet; Kumar, Viresh; Neogi, Sushanto (International Surgery Journal, 2020)
Liver is the most common organ involved in echinococcosis. Organs affected by E granulosus are the liver (63%), lungs (25%) and muscles (5%). Rest of the organs are rarely affected. Adrenal cysts are uncommon. Their size may range widely and the origin of large adrenal cysts is often difficult to distinguish from other organs, including the kidney, pancreas, spleen, and liver. A large right-sided adrenal cystic mass can rarely be mistaken for a hepatic cyst by imaging. In this report, authors have described an adrenal cyst in a 28 year old lady, who was diagnosed preoperatively to have a hepatic hydatid cyst but intraoperatively it was found to be of adrenal origin. The size of the adrenal cyst can vary from a few millimetres up to 50 cm in diameter. Majority of the adrenal cysts are unilateral, while 8-10% of those cysts have been noted to be present bilaterally. The majority of cases are diagnosed between the 3rd and 6th decades. Although uncommon, Adrenal cyst should be considered as one of the differential diagnosis of upper abdominal cysts. Surgical excision is advisable when the cysts are symptomatic, greater than 5 cm in diameter and in the case of suspecting malignancy.